THE FEATURE OF DUTCH DISEASE IN THE MONGOLIAN ECONOMY - Jamsranjav, Enkhbayar; Luvsandash, Oyuntsetseg (Journal of Business and Innovation (Бизнес & Инноваци), 2024)
In this paper Mongolia is one of the developing countries where a significant part of its economy is provided by using natural resources - especially from the mining sector. The Mongolian present situation is a period of fluctuation between advanced economic development and a way of decline, and it can be a reflection of the so-called “natural resource curse”. In general, the current natural resource dilemma causing the economic downturn is likely to be driven by external market forces such as mineral commodity prices volatility, and internal economic stresses which would result in a slowing growth, in particular, it appears to be caused by some effects of the Dutch disease.